Battle of the bad-breath bats - Bowles, David (David O.) (Bowles, David (David O.). 13th Street, 2020)
"Cousins Malia, Ivan, and Dante are visiting their aunt Lucy for the summer. But on their way to Gulf City's water park, they get lost on 13th Street. Only it's not a street at all. It's a strange world filled with dangerous beasts! Will the cousins find their way back to Aunt Lucy's?"--Page [4] of cover.